2019
DOI: 10.21833/ijaas.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Statistical impacts of interaction between mindset and engagement on Kaizen success: Empirical case among SMEs in Vietnam

Abstract: The current trend of international integration urges business organizations to continuously improve their competitive advantage for their survival and sustainable growth. And Kaizen has been a preferable approach in practice. This study aims at investigating the statistical impacts of the interactions between mindset and engagement of organization members on the Kaizen success among SMEs in Vietnam so that they can have proper actions and prioritize their operations within their available resources. It is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A case study shows that to continuously progress in the sustainable growth of a company, the Kaizen tool is implemented, and it was found that by applying this methodology the statistical impacts of the workers positively Framework of Global Transformations: Integration and Alliances for Integral Development", Hybrid Event, Buenos Aires -ARGENTINA, July 17 -21, 2023. 2 affect their commitment, mentality, and interaction, thus having better decision making and the tasks to be prioritized [10]. From another point of view, another case study performed an analysis and applied Kaizen methodology in a restaurant addressing several challenges in different operational procedures, which impair and influence customer satisfaction and company performance.…”
Section: B Kaizen In the Commercial Sectormentioning
confidence: 99%
“…A case study shows that to continuously progress in the sustainable growth of a company, the Kaizen tool is implemented, and it was found that by applying this methodology the statistical impacts of the workers positively Framework of Global Transformations: Integration and Alliances for Integral Development", Hybrid Event, Buenos Aires -ARGENTINA, July 17 -21, 2023. 2 affect their commitment, mentality, and interaction, thus having better decision making and the tasks to be prioritized [10]. From another point of view, another case study performed an analysis and applied Kaizen methodology in a restaurant addressing several challenges in different operational procedures, which impair and influence customer satisfaction and company performance.…”
Section: B Kaizen In the Commercial Sectormentioning
confidence: 99%